Bringing Children into the Sociology of Consumption: A Symbolic Consumption Perspective - Belinda Senooane; Johannes Wiid (Journal of Marketing and Consumer Behaviour in Emerging Markets)
This article explores children’s consumption practices from a sociology of consumption perspective. The aim is to discover whether South African children, in their consumption of clothing, engage in symbolic consumption and to identify the ways in which they do so. Existing studies on children and symbolic consumption have largely excluded African children, hence this study represents an attempt to include their voices in the conceptualisation of childhood consumer behaviour. Data were collected through a survey of 192 children aged 10–14, using a questionnaire developed from the literature on symbolic consumption. The article presents the design and implementation of a quantitative empirical study into children’s engagement in symbolic consumption. Exploratory factor analysis (EFA) was used to tease out the factors representing the ways in which children engage in symbolic consumption, while confirmatory factor analysis was used to verify the factor structure and test whether the data fit the model. The EFA revealed four factors that represent the ways in which children engage in symbolic consumption: identity, affiliation, perception, and image. The findings reveal that children use their clothing to create their individual identities, fit in with social groups, draw inferences about others through their clothing, and as a yardstick to gauge social image. This research furthers the enquiry into children as consumers while addressing the paucity of research related to African child consumers. The results of the study have implications for marketing practitioners, while also providing directions for future research.